2022
DOI: 10.14336/ad.2022.0826-1
|View full text |Cite
|
Sign up to set email alerts
|

Roles of Ependymal Cells in the Physiology and Pathology of the Central Nervous System

Abstract: Ependymal cells are indispensable components of the central nervous system (CNS). They originate from neuroepithelial cells of the neural plate and show heterogeneity, with at least three types that are localized in different locations of the CNS. As glial cells in the CNS, accumulating evidence demonstrates that ependymal cells play key roles in mammalian CNS development and normal physiological processes by controlling the production and flow of cerebrospinal fluid (CSF), brain metabolism, and waste clearanc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
15
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 138 publications
3
15
0
Order By: Relevance
“…Interactions within ependymal cells and oligodendrocytes were shown to decrease significantly with age, while interactions within astrocytes and from astrocytes to neurons significantly increased with age. This reflects the current understanding that the ependymal layer thins during aging and reactive astrocytes proliferate and interpose themselves within the ependymal cell layer [25, 26]. Oligodendrocyte numbers and function are also known to decrease with age while astrocyte interactions increase, which is shown in our findings [27, 28, 29].…”
Section: Resultssupporting
confidence: 88%
“…Interactions within ependymal cells and oligodendrocytes were shown to decrease significantly with age, while interactions within astrocytes and from astrocytes to neurons significantly increased with age. This reflects the current understanding that the ependymal layer thins during aging and reactive astrocytes proliferate and interpose themselves within the ependymal cell layer [25, 26]. Oligodendrocyte numbers and function are also known to decrease with age while astrocyte interactions increase, which is shown in our findings [27, 28, 29].…”
Section: Resultssupporting
confidence: 88%
“…PANTHER pathway enrichment analysis showed that these genes were significantly associated with specific pathways such as the metabotropic glutamate receptor group III pathway (P00039), Angiogenesis (P00005), the CCKR signaling map (P06959), Gonadotropin‐releasing hormone receptor pathway (P06664), Ionotropic glutamate receptor pathway (P00037), heterotrimeric G‐protein signaling pathway‐Gq alpha and Go alpha‐mediated pathway (P00027), and metabotropic glutamate receptor group I pathway (P00041) (Table S7). Hypergeometric tests showed that these pathways were particularly enriched in choroid plexus and ependymal cells (Figure S3) that function in cerebrospinal fluid (CSF) homeostasis and brain metabolism 67–70 . This suggested that placental REST played an influential role in the regulation and maintenance of CSF homeostasis and metabolism in the offspring brain.…”
Section: Resultsmentioning
confidence: 97%
“…The primary functions of these cells in the brain are to produce cerebrospinal fluid (CSF) and maintain metabolic homeostasis. [67][68][69][70] Signaling transduction in the brain is influenced by CSF, whose deregulation affects brain with behavioral changes. 92 The glutamatergic signaling genes associated with both the metabotropic (Gcoupled protein) as well as the ionotropic (ligand-gated ion channel) glutamate receptors (GluRs) were deregulated in the choroid plexus and ependymal cells.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations